Kajian Usaha Tani VUB Padi Sawah Toleran Kekeringan di Kota Bima - Irma Mardian; M Saleh Mokhtar; Eka Widiastuti (Seminar Nasional Lahan Suboptimal, 2021)
Mardian I, Mokhtar MS, Widiastuti E. 2021. Farming analyze of new superior variety drought tolerance of rice  in Bima City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 705-712.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).New superior varieties (VUB) of rice with high yield potential and drought tolerance  are genetically characteristic of rice to overcome drought stress that decrease rice productivity. The use of rice VUB is expected to increase crop productivity and farmer income. This study aimed to analyze rice farming and to obtain adaptability of high yield potential (VUB) rice in drought-potential environments. The assessment was conducted on June-September 2018 (MK II) at the Kawinda farmer group in Jatibaru Village, Asakota District, Bima City. The study was laid out with Randomized Complete Block Design (RCBD) with 3 replications. The treatments were 7 varieties (Inpari 38, Inpari 39, Inpari 41, Inpari 42, Inpari 43, IR 64 and Ciherang where last 2 varieties were always planted by farmers.  The results showed that Inpari 43, 41 dan 42 varieties found to be the highest productivity for 9,44 t/ha, 8,94 t/ha, 8,72 t/ha, respectively with farners’ profit  ranging from 21,045,600 IDR - 22,970,480/ha.  Thus 3 varieties of rice may the potential VUB and feasible  to be developed in Bima City.